Kitab Kuning: Warisan Keilmuan Ulama dan Kontekstualisasi Hukum Islam Nusantara - Damanhuri Damanhuri ('Anil Islam: Jurnal Kebudayaan dan Ilmu Keislaman, 2017)
This article attempts to describe the existence of the Kitab Kuning (Arabic Book) as a legacy of Islamic scholarship literacy which has an intellectual connection with earlier scholar and to see the contextualization of Islamic law in Nusantara. By Examining many library books related to the topic, including the work of Nusantara scholar, this article uses historical reviews and analyze it critically.The result shows that the existence of Kitab Kuning is not only to conserve and preserve the heritage of Islamic scholarship but also to be a signifier of one's intellectual capacity in understanding, interpreting and contextualizing the principles of Islamic law in order to respond social and cultural change. On the other hand, the contextualization of Islamic law in Nusantara is carried out in several ways; translating the works of jurisprudence, writing a commentary (syarḥ) from a prominent jurisprudence and writing his own works by keep referring to the authoritative sources of the Islamic school of earlier scholarly work.